PELATIHAN PENYUSUNAN PERATURAN NAGARI DI NAGARI SUNGAI BULUH TIMUR KECAMATAN BATANG ANAI - Syofiarti Syofiarti (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2018)
This article discusses the activities of the Nagari Rule Drafting Training in Nagari Sungai Buluh TimurKecamatan Batang Anai. From this activity revealed that there is still no understanding of nagari device inarranging Nagari Regulation. This is because that Nagari Sungai Buluh Timur is a new nagari ofpemekaran. So far, the existing nagari regulation only regulates the general matters only and has nottouched upon the special case in accordance with the meaning of regional autonomy. In this training themethod used is to provide a basic knowledge of the formation of the nagari rules and training on theprocedures for the formation of the nagari rules. The nagari regulations are made according to the needsof the nagari by forming small groups. The implementation of this activity received a very enthusiastic response from the nagari device. At the end of the activity between the participants with the Bagian HAN of the Faculty of Law Unand gave birth to a part commitment to accompany the coming arrangement of the next Nagari Sungai Buluh Timur.